P132 Design of an adaptive, phase 2, placebo-controlled, dose-ranging study to assess the efficacy and safety of AMG 570 in subjects with active SLE and inadequate response to standard of care therapy. (23rd March 2020) - Zhou, Lei; Wang, Hui; Jiang, Tony; Garces, Sandra; Cheng, Laurence E; Lenz, Rob; Kaur, Primal
Abstract : Background/Purpose: Current SLE treatment options have limited efficacy and potential toxicities that impede an individual's ability to remain on therapy. AMG 570 is a bispecific antibody inhibiting both ICOSL and BAFF that engages ICOSL on antigen-presenting cells (dendritic cells and B cells) and reduces circulating naïve B cells in healthy subjects. This phase 2 study will employ SLE drug screening and response-adaptive randomization (RAR) to optimize dose selection of AMG 570 in subjects with active SLE and inadequate response to standard of care (SOC) therapy (NCT04058028 ). Methods: In this adaptive, phase 2, placebo-controlled, dose-ranging study, subjects (N∼300, age 18–75 years) will be randomized to receive placebo or 1 of 3 doses of AMG 570 Q2W for 52 weeks, followed by 16 weeks of safety follow-up. The primary objective is to evaluate efficacy of AMG 570 compared with placebo at week 24 using the SLE Responder Index (SRI-4). Key secondary endpoints include SRI-4 at week 52 with oral corticosteroid (OCS) reduction (≥10 mg/day at baseline to ≤7.5 mg/day in weeks 44–52) and SRI-4 and Lupus Low Disease Activity State at week 52. Subjects will undergo 2 screening visits to fulfill criteria for active SLE and demonstrate adherence to prior SLE treatment including OCS, immunosuppressants, and/or immunomodulators. Blood screening tests will confirm detectable serum drug levels of baseline SOC medications. RAR aims to allocate more subjects to more efficacious doses while maintaining the placebo allocation constant; the randomization ratio could be adapted after interim analyses based on clinical efficacy. The trial includes interim analyses for futility using the Bayesian approach. Results: Study ongoing. Conclusion: This study will provide safety and efficacy data for AMG 570 compared with placebo, and its adaptive trial design aims to optimize development of a novel therapy for SLE patients with inadequate response to current SOC. Acknowledgments: Amgen Inc. sponsored this study.